Long-term evolution of pH and metals (Al, Fe, Mn, U) in pyrite-bearing waste rocks using reactive transport modeling: Dealing with stock and process uncertainties - Sophie Guillon; Pierre L'Hermite; Catherine Beaucaire; Nicolas Seigneur; Martine Leermakers; Benoit Reilé; Vincent Lagneau; Guillaume Kern; Antoine De Amorin; Michael Descostes (Journal of Geochemical Exploration, 2026)

Unveiling the sumatriptan dose-relief relationship - Clément Rigaut; Benoit Haut; Pierre Lambert; Jonathan Goole (European Journal of Clinical Pharmacology, 2026)

Designing perennial crop-based agroforestry systems: specificities, challenges, and opportunities - Anne Merot; Alexis Thoumazeau; Aude Alaphilippe; Margot Challand; Timothée Cheriere; Stéphane de Tourdonnet; Frédéric Gay; Marie Gosme; Marie-Hélène Jeuffroy; Pierre-Éric Lauri; Aurélie Metay; Martin Notaro; et al. (Agroforestry Systems, 2026)
Diversification of farming systems at plot scale is increasingly seen as an essential option to meet agriculture sustainability challenges and support agroecological transition. Significant progress has been made in recent years on methods for designing diversified cropping systems based on annual crops. However, few methods have been tested for designing diversified cropping systems based on perennial crops, and in particular perennial crop-based agroforestry systems, despite their important dietary and economic roles in the world. In this study, we argue that the characteristics of perennial crops induce specific structural and functional changes that impact the design process. We identified four key concepts for the design of diversified perennial crop-based agroforestry systems: (i) the targeted productivity must be considered over the long term and at the plot level, and encompass not only the productive and non-productive stages of perennial crops but also of associated plants; (ii) these systems will eventually face shocks and crisis in their lifetime, so they should be designed with resilience and adaptability in mind; (iii) initial designs will necessarily evolve throughout the long lifespan of perennial crops, and so a combination of de novo design from scratch and step-by-step design approaches for regeneration or transformation will be required; and (iv) due to the high complexity of these systems and the difficulty of setting up trials, the design process should draw from a range of knowledges from academics and practitioners and hybrid them. These four key features show that perennial crops offer distinct opportunities for the design of sustainable diversified cropping systems, but also face specific challenges that require more transdisciplinary research.

Influence of redox atmospheres on selenate retention by mackinawite, magnetite and pyrite - Kaifeng Wang; Alejandro Fernandez-Martinez; Nicolas Menguy; Laura Simonelli; Benoit Madé; Pierre Hénocq; Bin Ma; Laurent Charlet (Journal of Hazardous Materials, 2026)

Voacangine/coronaridine hydroxylases catalyze C19-hydroxylation in iboga alkaloid synthesis - Ana Luisa Lopez-Vazquez; Mickael Durand; Caroline Birer-Williams; Elfie Perdereau; Emeline Marais; Thomas Perrot; Audrey Oudin; Arnaud Lanoue; Benoit St-Pierre; Nicolas Papon; Georges Massiot; Chao Sun; et al. (Planta, 2026)

Burden of respiratory syncytial virus (RSV) vs. influenza (A/B) in adults ≥ 50 years: a Pre-COVID-19 multicenter retrospective study - Benjamin Davido; Elyanne Gault; Djillali Annane; Sebastien Beaune; Jennifer Dumoulin; Pierre de Truchis; Azzam Saleh-Mghir; Karim Jaffal; Benoit Lemarié (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Development of a scalable design for biofuel production from green macroalgae hydrolysates - Hayet Djelal; Alaa Salma; Walaa Sayed; Audrey Cabrol; Maud Benoit; Amance Corat; Abdeltif Amrane; Ronan Pierre (Algal Research, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Bubbling regimes in water electrolysis using a membraneless micro-electrolyzer - Mohammad Torkian; Benoit Haut; Pierre Van de Velde; Benoit Scheid (Chemical Engineering Journal, 2025)

Biological ion exchange for natural organic matter removal from drinking water - Karl Zimmermann; Klaas Schoutteten; Zhen Liu; William Chen; Pierre Bérubé; Madjid Mohseni; Benoit Barbeau (Water Research, 2025)

Lithic analysis of the North African Middle Stone Age from the Rhafas cave sequence - Benoit Longet; Jean-Pierre Bracco; El Hassan Talbi; Jacques Collina-Girard; Abdeljalil Bouzouggar (Quaternary International, 2025)

HERFD-XAS evidence for an octahedrally coordinated CoSn-polysulfide precursor as a probe for the mechanism of pyrite formation - Qianyu Deng; Pierre Le Pape; Julie Aufort; Marc Blanchard; Benoit Baptiste; Ludovic Delbes; Camille Baya; Farid Juillot; George Ona-Nguema; Nicolas Menguy; Jean-Michel Guigner; Olivier Proux; et al. (Geochimica et Cosmochimica Acta, 2025)

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

Speciation of uranium and radium during the treatment of acidic waters from legacy-mine (Le Cellier, France) - Pascal E. Reiller; Pierre L’Hermite; Valérie Plagnes; Anne Jost; Benoit Reilé; Martine Leermakers; Michaël Descostes (Journal of Environmental Chemical Engineering, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Life history stage effects on alert and flight initiation distances in king penguins (Aptenodytes patagonicus) - Tracey L. Hammer; Pierre Bize; Benoit Gineste; Jean-Patrice Robin; René Groscolas; Vincent A. Viblanc (Behavioural Processes, 2025)

Biophysical characterization and typology of interactions in the agroforests of central cameroon - Alex Bruno Dong Etchike; Fawa Guidawa; Marie Louise Avana Tchientcheu; Victor François Nguetsop; Martin Benoit Ngassoum; Pierre Marie Mapongmetsem (Agroforestry Systems, 2025)

Measurement and modelling of water flows and pesticide leaching under low input cropping systems - Laure Mamy; Jesús M. Marín-Benito; Lionel Alletto; Eric Justes; Marjorie Ubertosi; Nicolas Munier-Jolain; Bernard Nicolardot; Catherine Bonnet; Julien Moeys; Mats Larsbo; Valérie Pot; Carole Bedos; et al. (Science of The Total Environment, 2024)

Towards sustainable construction in Cameroon : impact of tropical plant fibers on the performance of compressed earth bricks - Fabien Betene Ebanda; Armel Edwige Mewoli; Abel Emmanuel Njom; Marius Tony Kibong; Pierre Marcel Anicet Noah; Benoit Ndiwé; Marie Josette Ndengue; Sandrine Olive Biloa Otiti; Jean Raymond Lucien Meva’a; Atangana Ateba (Innovative Infrastructure Solutions, 2024)

Cardiac electrical and functional activity following an outdoor cold-water swimming event - Victorien Faivre-Rampant; Corentin Hingrand; A. Mezanger; Eric Saloux; Pierre Ollitrault; Simon Alvado; Hervé Normand; Igor B. Mekjavic; Thibaud Collet; Benoit Mauvieux; Joffrey Drigny; Amir Hodzic (Journal of Thermal Biology, 2024)

Breaching of the Sillon de Talbert gravel spit (North Brittany, France) and coastal flooding risk assessment - Pierre Stéphan; Serge Suanez; Thomas Guérin; Aurélie Rivier; Laurent Leballeur; Benoit Waeles; Jérôme Ammann; Julien Houron (Geomorphology, 2024)

Initiation and development of tectonic stylolite – Vein system in micritic limestone (Les Matelles, France) - Grégory Ballas; Suzanne Raynaud; Michel Lopez; Emilien Oliot; Jean-Pierre Sizun; Jacinthe Caillaud; Fabrice Barou; Benoit Ildefonse (Journal of Structural Geology, 2024)

Influence of karst conduit’s geometry and morphology on 3D flow and transport processes: Insights from 3D tracer tests and numerical modelling - Mohammed Aliouache; Pierre Fischer; Pascal Brunet; Lionel Lapierre; Benoit Ropars; Frank Vasseur; Hervé Jourde (Journal of Hydrology, 2024)

Modern human atlas ranges of motion and Neanderthal estimations - Carlos A. Palancar; Markus Bastir; Antonio Rosas; Pierre-Michel Dugailly; Stefan Schlager; Benoit Beyer (Journal of Human Evolution, 2024)

Ozone exposure induces metabolic stress and olfactory memory disturbance in honey bees. - Fabien Démares; Laëtitia Gibert; Benoit Lapeyre; Pierre Creusot; David Renault; Magali Proffit (Chemosphere, 2024)

Combining RADseq and contact zone analysis to decipher cryptic diversification in reptiles: Insights from the Spiny‐footed Lizard (Reptilia, Lacertidae) - Paul Doniol‐Valcroze; Loïs Rancilhac; José‐Carlos Brito; Aurélien Miralles; Philippe Geniez; Laure Benoit; Anne Loiseau; Raphaël Leblois; Christophe Dufresnes; Pierre‐André Crochet (Zoologica Scripta, 2024)
Uncertainties on species taxonomy and distribution are major factors hampering efficient conservation planning in the current context of biodiversity erosion, even concerning widespread and abundant species in relatively well‐studied regions. Species delimitation have long been based on phylogenetic analyses of a small number of standard markers, but accurate lineage identification through this approach can be hampered by incomplete lineage sorting, introgression or isolation by distance. In that context, analyses of introgression patterns at secondary contact zones offer an interesting alternative by allowing a direct estimation of reproductive isolation, especially when using genome‐wide markers. Here, we investigated a contact zone between two genetic groups of the Spiny‐footed Lizard Acanthodactylus erythrurus (Schinz, 1833) in Morocco, whose status as separate lineages remained disputed in previous multilocus studies. Based on thousands of genome‐wide markers obtained through a RADseq approach, we confirmed that they represent distinct evolutionary lineages. Furthermore, the transition at their contact zone was very steep, with spatially restricted gene flow, highlighting levels of reproductive isolation consistent with species‐level lineages. Our study further illustrates the power of RADseq‐based studies of contact zones to understand cryptic diversity in non‐model organisms.

Influence of typology and management practices on water pCO 2 and atmospheric CO2 fluxes over two temperate shelf–estuary–marsh water continuums - Jérémy Mayen; Pierre Polsenaere; Aurore Regaudie de Gioux; Christine Dupuy; Marie Vagner; Jean-Christophe Lemesle; Benoit Poitevin; Philippe Souchu (Regional Studies in Marine Science, 2023)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Disentangling the “many-eyes”, “dilution effect”, “selfish herd”, and “distracted prey” hypotheses in shaping alert and flight initiation distance in a colonial seabird - Tracey L. Hammer; Pierre Bize; Benoit Gineste; Jean-Patrice Robin; René Groscolas; Vincent A. Viblanc (Behavioural Processes, 2023)

Montagne Pelée volcano (Martinique, in the French Lesser Antilles) hydrogeological system revealed by high-resolution helicopter-borne electromagnetic imagery - Benoit Vittecoq; Pierre-Alexandre Reninger; Vincent Bellier; Anne-Lise Taïlamé; Laureen Nacimento; Emile Gros; Sophie Violette (Hydrogeology Journal, 2023)
Montagne Pelée, on the French island of Martinique, eastern Caribbean Sea, has been one of the deadliest volcanoes in the world, with 30,000 victims following the 1902 eruption. Thousands of people still live nearby, and this volcano is a strategic “water tank” for Martinique Island, providing 40% of the island’s water supply. This research aimed to better understand its hydrogeological functioning and the relationship with its complex volcanological evolution, taking advantage of a high-resolution helicopter-borne geophysical survey correlated with hydrogeological data from the boreholes and springs databases. Electromagnetic data, correlated with hydrogeological data, allowed for the identification of unsaturated zones, aquifers, and seawater intrusions, as well as the main geological units. In addition, data synthesised from pumping tests revealed that the older the unconsolidated pyroclastic deposits, the lower their hydraulic conductivity. The structural asymmetry between the northeastern and southwestern volcano flanks impacts its hydrogeological functioning. Consequently, the Montagne Pelée hydrogeological conceptual model is marked by several distinguishable aquifers. The upper perched aquifer within recent lava domes is directly involved in, and impacted by, phreatic eruptions, and it supports low flowrate springs. The remaining effective rainfall infiltrates to depth and recharges the hydrothermal system through vertical fractures. The other aquifers are categorized into three groups: northeastern, southeastern and southwestern flank aquifers. This research is a new step toward a better understanding of the Lesser Antilles volcanoes and more broadly of the central and proximal parts of the andesitic active volcanoes.

Spatial localization of monoterpenoid indole alkaloids in Rauvolfia tetraphylla by high resolution mass spectrometry imaging - Marcus Daniel Brandbjerg Bohn Lorensen; Nanna Bjarnholt; Benoit St-Pierre; Sarah Heinicke; Vincent Courdavault; Sarah O'Connor; Christian Janfelt (Phytochemistry, 2023)

Is a dissipation half-life of 5 years for chlordecone in soils of the French West Indies relevant? - Pierre-Loïc Saaidi; Olivier Grünberger; Anatja Samouëlian; Yves Le Roux; Antoine Richard; Damien A. Devault; Cyril Feidt; Pierre Benoit; Olivier Evrard; Gwenaël Imfeld; Christophe Mouvet; Marc Voltz (Environmental Pollution, 2023)

Data quality control considerations in multivariate environmental monitoring: experience of the French coastal network SOMLIT - Elsa Breton; Nicolas Savoye; Peggy Rimmelin-Maury; Benoit Sautour; Eric Goberville; Arnaud Lheureux; Thierry Cariou; Sophie Ferreira; Hélène Agogué; Samir Alliouane; Fabien Aubert; Sébastien Aubin; et al. (Frontiers in Marine Science, 2023)
Introduction While crucial to ensuring the production of accurate and high-quality data—and to avoid erroneous conclusions—data quality control (QC) in environmental monitoring datasets is still poorly documented. Methods With a focus on annual inter-laboratory comparison (ILC) exercises performed in the context of the French coastal monitoring SOMLIT network, we share here a pragmatic approach to QC, which allows the calculation of systematic and random errors, measurement uncertainty, and individual performance. After an overview of the different QC actions applied to fulfill requirements for quality and competence, we report equipment, accommodation, design of the ILC exercises, and statistical methodology specially adapted to small environmental networks (<20 laboratories) and multivariate datasets. Finally, the expanded uncertainty of measurement for 20 environmental variables routinely measured by SOMLIT from discrete sampling—including Essential Ocean Variables—is provided. Results, Discussion, Conclusion The examination of the temporal variations (2001–2021) in the repeatability, reproducibility, and trueness of the SOMLIT network over time confirms the essential role of ILC exercises as a tool for the continuous improvement of data quality in environmental monitoring datasets.

Current observed global mean sea level rise and acceleration estimated from satellite altimetry and the associated measurement uncertainty - Adrien Guérou; Benoit Meyssignac; Pierre Prandi; Michaël Ablain; Aurélien Ribes; François Bignalet-Cazalet (Ocean Science, 2023)
We present the latest release of the global mean sea level (GMSL) record produced by the French space agency Centre National d’Etudes Spatiales (CNES) and distributed on the AVISO+ website. This dataset is based on reprocessed along-track data, so-called L2P 21, of the reference missions TOPEX/Poseidon (TP) and Jason-1, Jason-2 and Jason-3. The L2P 21 CNES/AVISO+ GMSL record covers the period January 1993 to December 2021 and is now delivered with an estimate of its measurement uncertainties following the method presented in Ablain et al. (2019). Based on the latest calibration (Cal) and validation (Val) knowledge, we updated the uncertainty budget of the reference altimetry mission measurements and demonstrate that the CNES/AVISO+ GMSL record now achieves stability of performances of ± 0.3 mm yr−1 at the 90 % confidence level (C.L.) for its trend and ±0.05 mm yr−2 (90 % C.L.) for its acceleration over the 29 years of the altimetry record. Thanks to an analysis of the relative contribution of each measurement uncertainty budget contributor, i.e. the altimeter, the radiometer, the orbit determination and the geophysical corrections, we identified the current limiting factors to the GMSL monitoring stability and accuracy. We find that the radiometer wet troposphere correction (WTC) and the high-frequency errors with timescales shorter than 1 year are the major contributors to the GMSL measurement uncertainty over periods of 10 years (30 %–70 %), for both the trend and acceleration estimations. For longer periods of 20 years, the TP data quality is still a limitation, but more interestingly, the International Terrestrial Reference Frame (ITRF) realization uncertainties becomes dominant over all the other sources of uncertainty. Such a finding challenges the altimetry observing system as it is designed today and highlights clear topics of research to be explored in the future to help the altimetry community to improve the GMSL measurement accuracy and stability.

A bibliometric analysis of the Global Reporting Initiative (GRI): global trends in developed and developing countries - Benoit Mougenot; Jean-Pierre Doussoulin (Environment, Development and Sustainability, 2023)

Building capacities for the design of agroecological landscapes: The added-value of Landscape Monitoring Networks - Sandrine Petit; Audrey Alignier; Roland Allart; Stéphanie Aviron; Hugues Boussard; Pierre Franck; Caroline Gibert; Sylvie Ladet; Claire Lavigne; Lou Lecuyer; Maxime Moncamp; Lucile Muneret; et al. (Agriculture, Ecosystems & Environment, 2023)

Transformation of PPCPs in the environment: Review of knowledge and classification of pathways according to parent molecule structures - Kevin Bonnot; Pierre Benoit; Laure Mamy; Dominique Patureau (Critical Reviews in Environmental Science and Technology, 2023)

The ecologically relevant genetics of plant–plant interactions - Claude Becker; Richard Berthomé; Philippe Delavault; Timothée Flutre; Hélène Fréville; Stéphanie Gibot-Leclerc; Valérie Le Corre; Jean-Benoit Morel; Nathalie Moutier; Stéphane Muños; Céline Richard-Molard; James Westwood; et al. (Trends in Plant Science, 2023)

Trace elements, dioxins and PCBs in different fish species and marine regions: Importance of the taxon and regional features - Aourell Mauffret; Tiphaine Chouvelon; Nathalie Wessel; Pierre Cresson; Daniela Bănaru; Jérôme Baudrier; Paco Bustamante; Rachida Chekri; Petru Jitaru; François Le Loc'h; Benoit Mialet; Vincent Vaccher; et al. (Environmental Research, 2023)

Changes in cardiac function following a speed ascent to the top of Europe at 4808 m - Benoit Champigneulle; Stéphane Doutreleau; Sébastien Baillieul; Julien Vincent Brugniaux; Paul Robach; Pierre Bouzat; Samuel Verges (European Journal of Applied Physiology, 2022)

Effect of a speed ascent to the top of Europe on cognitive function in elite climbers - Benoit Champigneulle; Karen Davranche; Julien Vincent Brugniaux; Sébastien Baillieul; Thibault Gajdos; Stéphane Doutreleau; Paul Robach; Pierre Bouzat; Samuel Verges (European Journal of Applied Physiology, 2022)

Lyme arthritis in Western Europe: a multicentre retrospective study - Clémence Corre; Guillaume Coiffier; Benoit Le Goff; Marine Ferreyra; Xavier Guennic; Solène Patrat-Delon; Brigitte Degeilh; Jean-David Albert; Pierre Tattevin (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Photodegradation of methotrexate in aqueous solution: degradation kinetics and identification of transformation products - Anaïs Espinosa; Sylvie Nélieu; Pascale Lieben; Charles Skarbek; Raphaël Labruère; Pierre Benoit (Environmental Science and Pollution Research, 2022)

Conceptual evolution of the bioeconomy: a bibliometric analysis - Benoit Mougenot; Jean-Pierre Doussoulin (Environment, Development and Sustainability, 2022)

Soil and plant health in relation to dynamic sustainment of Eh and pH homeostasis: A review - Olivier Husson; Jean-Pierre Sarthou; Lydia Bousset; Alain Ratnadass; Hans-Peter Schmidt; John Kempf; Benoit Husson; Sophie Tingry; Jean-Noël Aubertot; Jean-Philippe Deguine; François-Régis Goebel; Jay Ram Lamichhane (Plant and Soil, 2021)

Joint species distributions reveal the combined effects of host plants, abiotic factors and species competition as drivers of species abundances in fruit flies - Benoit Facon; Abir Hafsi; Maud Charlery de la Masselière; Stéphane Robin; François Massol; Maxime Dubart; Julien Chiquet; Enric Frago; Frédéric Chiroleu; Pierre‐François Duyck; Virginie Ravigné (Ecology Letters, 2021)
The relative importance of ecological factors and species interactions for shaping species distributions is still debated. The realised niches of eight sympatric tephritid fruit flies were inferred from field abundance data using joint species distribution modelling and network inference, on the whole community and separately on three host plant groups. These estimates were then confronted the fundamental niches of seven fly species estimated through laboratory‐measured fitnesses on host plants. Species abundances depended on host plants, followed by climatic factors, with a dose of competition between species sharing host plants. The relative importance of these factors mildly changed among the three host plant groups. Despite overlapping fundamental niches, specialists and generalists had almost distinct realised niches, with possible competitive exclusion of generalists by specialists on Cucurbitaceae. They had different assembly rules: Specialists were mainly influenced by their adaptation to host plants, while generalist abundances varied regardless of their fundamental host use.

Agreement between the categorization of isolates of Aeromonas salmonicida and Yersinia ruckeri by disc diffusion and MIC tests performed at 22℃ - Sandrine Baron; Emeline Larvor; Eric Jouy; Isabelle Kempf; Sophie Le Bouquin; Claire Chauvin; Pierre‐Marie Boitard; Matthieu Jamin; Alain Le Breton; Benoit Thuillier; Peter Smith (Journal of Fish Diseases, 2021)
Standard disc diffusion and MIC test procedure were used to investigate the susceptibility of two hundred and fifty‐one isolates collected from infected fish in France to florfenicol, oxolinic acid and tetracycline. The tests were performed at 22 ± 2℃ and for the 177 Yersinia rucker i they were read after 24–28 hr incubation and for the 74 Aeromonas salmonicida isolates they were read after 44–48 hr. Applying epidemiological cut‐off values to the susceptibility data generated in these tests, the isolates were categorized as wild‐type or non‐wild‐type. The agent‐specific categories into each isolate were placed on the basis of the data generated by the two methods were in agreement in 98% of the determinations made. It is argued that, with respect to categorising isolates, disc diffusion and MIC methods can be considered as equally valid at this temperature and after both periods of incubation.

The climatic debt is growing in the understorey of temperate forests: Stand characteristics matter - Benoit Richard; Jean‐Luc Dupouey; Emmanuel Corcket; Didier Alard; Frédéric Archaux; Michaël Aubert; Vincent Boulanger; François Gillet; Estelle Langlois; Sébastien Macé; Pierre Montpied; Thérèse Beaufils; et al. (Global Ecology and Biogeography, 2021)
Aim Climate warming reshuffles biological assemblages towards less cold‐adapted but more warm‐adapted species, a process coined thermophilization. However, the velocity at which this process is happening generally lags behind the velocity of climate change, generating a climatic debt the temporal dynamics of which remain misunderstood. Relying on high‐resolution time series of vegetation data from a long‐term monitoring network of permanent forest plots, we aim at quantifying the temporal dynamics – up to a yearly resolution – of the climatic debt in the understorey of temperate forests before identifying the key determinants that modulate it. Location France. Time period 1995–2017. Taxa studied Vascular plants. Methods We used the community temperature index (CTI) to produce a time series of understorey plant community thermophilization, which we subsequently compared to a time series of mean annual temperature changes over the same period and for the same sites. The direction and magnitude of the difference (i.e., the climatic debt) was finally analysed using linear mixed‐effect models to assess the relative contributions of abiotic and biotic determinants, including forest stand characteristics. Results We found a significant increase in CTI values over time (0.08–0.09 °C/decade), whereas the velocity of mean annual temperature changes was three times higher over the same period (0.22–0.28 °C/decade). Hence, the climatic debt increased over time and was greater in forest stands with higher basal area or older trees as well as under warmer macroclimate. By contrast, a greater frequency of anthropogenic disturbances decreased the climatic debt, while natural disturbances and herbivory had no impact. Conclusions Although often overlooked in understanding the climatic debt of forest biodiversity, changes in forest stand characteristics may modulate the climatic debt by locally modifying microclimatic conditions. Notably, the buffering effect of the upper canopy layer implies microclimate dynamics that may provide more time for understorey plant communities to locally adapt.

Stewardship program on carbapenem prescriptions in a tertiary hospital for adults and children in France: a cohort study - Julie Poline; Martine Postaire; Perrine Parize; Benoit Pilmis; Emmanuelle Bille; Jean Ralph Zahar; Pierre Frange; Jérémie F. Cohen; Olivier Lortholary; Julie Toubiana (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Adsorption and degradation of the herbicide nicosulfuron in a stagnic Luvisol and Vermic Umbrisol cultivated under conventional or conservation agriculture - Sixtine Cueff; Lionel Alletto; Valérie Dumény; Pierre Benoit; Valérie Pot (Environmental Science and Pollution Research, 2021)

Can N 2 O emissions offset the benefits from soil organic carbon storage? - Bertrand Guenet; Benoit Gabrielle; Claire Chenu; Dominique Arrouays; Jérôme Balesdent; Martial Bernoux; Elisa Bruni; Jean‐Pierre Caliman; Rémi Cardinael; Songchao Chen; Philippe Ciais; Dominique Desbois; et al. (Global Change Biology, 2021)
To respect the Paris agreement targeting a limitation of global warming below 2°C by 2100, and possibly below 1.5°C, drastic reductions of greenhouse gas emissions are mandatory but not sufficient. Large‐scale deployment of other climate mitigation strategies is also necessary. Among these, increasing soil organic carbon (SOC) stocks is an important lever because carbon in soils can be stored for long periods and land management options to achieve this already exist and have been widely tested. However, agricultural soils are also an important source of nitrous oxide (N 2 O), a powerful greenhouse gas, and increasing SOC may influence N 2 O emissions, likely causing an increase in many cases, thus tending to offset the climate change benefit from increased SOC storage. Here we review the main agricultural management options for increasing SOC stocks. We evaluate the amount of SOC that can be stored as well as resulting changes in N 2 O emissions to better estimate the climate benefits of these management options. Based on quantitative data obtained from published meta‐analyses and from our current level of understanding, we conclude that the climate mitigation induced by increased SOC storage is generally overestimated if associated N 2 O emissions are not considered but, with the exception of reduced tillage, is never fully offset. Some options (e.g. biochar or non‐pyrogenic C amendment application) may even decrease N 2 O emissions.

Environmental and human health issues related to long-term contamination by chlordecone in the French Caribbean - Pierre Benoit; Jean Pierre Cravedi; Jean-Claude Desenclos; Christophe Mouvet; Guido Rychen; Michel Samson (Environmental Science and Pollution Research, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Heterogeneity of the rice microbial community of the Chinese centuries‐old Honghe Hani rice terraces system - Pascal Alonso; Laurence Blondin; Pierre Gladieux; Frédéric Mahé; Hervé Sanguin; Romain Ferdinand; Denis Filloux; Eric Desmarais; Frédérique Cerqueira; Baihui Jin; Huichuan Huang; Xiahong He; et al. (Environmental Microbiology, 2020)
Summary The Honghe Hani rice terraces system (HHRTS) is a traditional rice cultivation system where Hani people cultivate remarkably diverse rice varieties. Recent introductions of modern rice varieties to the HHRTS have significantly increased the severity of rice diseases within the terraces. Here, we determine the impacts of these recent introductions on the composition of the rice‐associated microbial communities. We confirm that the HHRTS contains a range of both traditional HHRTS landraces and introduced modern rice varieties and find differences between the microbial communities of these two groups. However, this introduction of modern rice varieties has not strongly impacted the overall diversity of the HHRTS rice microbial community. Furthermore, we find that the rice varieties (i.e. groups of closely related genotypes) have significantly structured the rice microbial community composition (accounting for 15%–22% of the variance) and that the core microbial community of HHRTS rice plants represents less than 3.3% of all the microbial taxa identified. Collectively, our study suggests a highly diverse HHRTS rice holobiont (host with its associated microbes) where the diversity of rice hosts mirrors the diversity of their microbial communities. Further studies will be needed to better determine how such changes might impact the sustainability of the HHRTS.

Non‐invasive functional exploration techniques for bivalves with applications to pearl oyster Pinctada margaritifera - Gilles Le Moullac; Claude Soyez; Pierre Lyonnard; Sébastien Chabrier; Léo Milhade; Yannick Gueguen; Benoit Beliaeff (Reviews in Aquaculture, 2020)
Non‐invasive functional exploration techniques can provide information on different aspects of general organism functioning and, unlike lethal or invasive techniques, allow individual organisms to be monitored for as long as necessary. For bivalves, a fairly wide variety of methods and instrumental means exist allowing physiology to be assessed on‐line while keeping animals alive and intact. The current range of non‐invasive techniques for bivalves consists of systems for measuring metabolic flows and valve activity, which can be used on bivalve molluscs for as long as an individual animal's characteristics (e.g. size) make this technically feasible. In this paper, we present some of these non‐invasive techniques with applications for pearl oyster and list other potentially promising techniques. We also focus on a unique method we developed specifically for to record the pearl rotation characteristics within pearl oysters. This article presents the state of the art in non‐invasive functional exploration techniques. We hope that the information provided here will be useful to physiologists of bivalve marine molluscs through the tools and applications presented here or other future approaches based on them.

Genome wide association mapping for resistance to multiple fungal pathogens in a panel issued from a broad composite cross-population of tetraploid wheat Triticum turgidum - Elsa Ballini; Muriel Tavaud; Aurélie Ducasse; Dimitri Sanchez; Etienne Paux; Jonathan Kitt; Gilles Charmet; Delphine Audigeos; Pierre Roumet; Jacques David; Jean-Benoit Morel (Euphytica, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Very Slow Creep Tests on Salt Samples - Pierre Bérest; Hakim Gharbi; Benoit Brouard; Dieter Brückner; Kerry DeVries; Grégoire Hévin; Gerd Hofer; Christopher Spiers; Janos Urai (Rock Mechanics and Rock Engineering, 2019)

Transcriptomic dissection of Bradyrhizobium sp. strain ORS285 in symbiosis with Aeschynomene spp. inducing different bacteroid morphotypes with contrasted symbiotic efficiency - Florian Lamouche; Djamel Gully; Anaïs Chaumeret; Nico Nouwen; Camille Verly; Olivier Pierre; Coline Sciallano; Joël Fardoux; Christian Jeudy; Attila Szücs; Samuel Mondy; Christophe Salon; et al. (Environmental Microbiology, 2019)
Summary To circumvent the paucity of nitrogen sources in the soil legume plants establish a symbiotic interaction with nitrogen‐fixing soil bacteria called rhizobia. During symbiosis, the plants form root organs called nodules, where bacteria are housed intracellularly and become active nitrogen fixers known as bacteroids. Depending on their host plant, bacteroids can adopt different morphotypes, being either unmodified (U), elongated (E) or spherical (S). E‐ and S‐type bacteroids undergo a terminal differentiation leading to irreversible morphological changes and DNA endoreduplication. Previous studies suggest that differentiated bacteroids display an increased symbiotic efficiency (E > U and S > U). In this study, we used a combination of Aeschynomene species inducing E‐ or S‐type bacteroids in symbiosis with Bradyrhizobium sp. ORS285 to show that S‐type bacteroids present a better symbiotic efficiency than E‐type bacteroids. We performed a transcriptomic analysis on E‐ and S‐type bacteroids formed by Aeschynomene afraspera and Aeschynomene indica nodules and identified the bacterial functions activated in bacteroids and specific to each bacteroid type. Extending the expression analysis in E‐ and S‐type bacteroids in other Aeschynomene species by qRT‐PCR on selected genes from the transcriptome analysis narrowed down the set of bacteroid morphotype‐specific genes. Functional analysis of a selected subset of 31 bacteroid‐induced or morphotype‐specific genes revealed no symbiotic phenotypes in the mutants. This highlights the robustness of the symbiotic program but could also indicate that the bacterial response to the plant environment is partially anticipatory or even maladaptive. Our analysis confirms the correlation between differentiation and efficiency of the bacteroids and provides a framework for the identification of bacterial functions that affect the efficiency of bacteroids.© 2018 Society for Applied Microbiology and John Wiley & Sons Ltd

Observing System Evaluation Based on Ocean Data Assimilation and Prediction Systems: On-Going Challenges and a Future Vision for Designing and Supporting Ocean Observational Networks - Yosuke Fujii; Elisabeth Rémy; Hao Zuo; Peter Oke; George Halliwell; Florent Gasparin; Mounir Benkiran; Nora Loose; James Cummings; Jiping Xie; Yan Xue; Shuhei Masuda; et al. (Frontiers in Marine Science, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Response of Scotian Shelf silver hake ( Merluccius bilinearis ) to environmental variability - Daniel Reed; Stéphane Plourde; Adam Cook; Pierre Pepin; Benoit Casault; Caroline Lehoux; Catherine Johnson (Fisheries Oceanography, 2019)
Commercially‐exploited fish populations are not only shaped by fishing pressure, but also by the dynamics of their environment. By quantifying the influence of environmental variability, fisheries management advice can be improved and uncertainties reduced. To this end, we developed statistical models of the response of Scotian Shelf silver hake stock metrics to variability in zooplankton community composition and phenology over the past 18 years and in the physical environment since 1985. Dominant modes of variability in these pelagic habitat indicators were characterized using principal component analysis, and the relationships of silver hake condition, abundance, and recruitment to pelagic habitat variability were assessed using generalized additive models. Condition was largely modulated by the onset and duration of the spring bloom, which controls food availability. In contrast, adult abundance was governed by composition of the zooplankton community and bottom‐water temperature, which dictates the distribution of silver hake. Finally, recruitment was affected by both thermal conditions and food availability. Our results presented here form the basis for qualitative assessment of ecosystem attributes and the influence on silver hake stock productivity.

Jumper’s knee mechanical consequences in professional basketball players: the “Camel’s Back curve” - Marc Dauty; Pierre Menu; Thomas Garraud; Olivier Mesland; Thibaud Berlivet; Benoit Metayer; Alban Fouasson-Chailloux (European Journal of Applied Physiology, 2019)

Inbreeding tolerance as a pre‐adapted trait for invasion success in the invasive ant Brachyponera chinensis - Pierre‐André Eyer; Kenji Matsuura; Edward L. Vargo; Kazuya Kobayashi; Toshihisa Yashiro; Wataru Suehiro; Chihiro Himuro; Tomoyuki Yokoi; Benoit Guénard; Robert R. Dunn; Kazuki Tsuji (Molecular Ecology, 2018)
Identifying traits that facilitate species introductions and successful invasions of ecosystems represents a key issue in ecology. Following their establishment into new environments, many non‐native species exhibit phenotypic plasticity with post‐introduction changes in behaviour, morphology or life history traits that allow them to overcome the presumed loss of genetic diversity resulting in inbreeding and reduced adaptive potential. Here, we present a unique strategy in the invasive ant Brachyponera chinensis (Emery) , in which inbreeding tolerance is a pre‐adapted trait for invasion success, allowing this ant to cope with genetic depletion following a genetic bottleneck. We report for the first time that inbreeding is not a consequence of the founder effect following introduction, but it is due to mating between sister queens and their brothers that pre‐exists in native populations which may have helped it circumvent the cost of invasion. We show that a genetic bottleneck does not affect the genetic diversity or the level of heterozygosity within colonies and suggest that generations of sib‐mating in native populations may have reduced inbreeding depression through purifying selection of deleterious alleles. This work highlights how a unique life history may pre‐adapt some species for biological invasions.

Evaluation of the mineralizing potential of the Mbengwi plutonics, Northwestern Cameroon, Central Africa - Benoît Joseph Mbassa; Emmanuel Njonfang; Michel Grégoire; Zénon Itiga; Pierre Kamgang; Mathieu Benoit; Paul Désiré Ndjigui; Caroline Neh Ngwa; Junior Désiré Nolla (Arabian Journal of Geosciences, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Multi-Beam Echo Sounders–INS Automatic Latency Calibration - Rabine Keyetieu; Nicolas Seube; Vignyl Djine; Gael Roue; Benoit Clement; Pierre Bosser (Marine Geodesy, 2018)

Suitability of a lumped rainfall–runoff model for flashy tropical watersheds in New Caledonia - Térence Desclaux; Hugues Lemonnier; Pierre Genthon; Benoit Soulard; Romain Le Gendre (Hydrological Sciences Journal, 2018)

Explaining the accelerated degradation of ciprofloxacin, sulfamethazine, and erythromycin in different soil exposure scenarios by their aqueous extractability - Anaïs Goulas; Lyne Sabourin; Farah Asghar; Claire-Sophie Haudin; Pierre Benoit; Edward Topp (Environmental Science and Pollution Research, 2018)

Hyperspectral core logging for fire reconstruction studies - Antonin Van Exem; Maxime Debret; Yoann Copard; Boris Vannière; Pierre Sabatier; Stephane Marcotte; Benoit Laignel; Jean-Louis Reyss; Marc Desmet (Journal of Paleolimnology, 2018)

Clustering pesticides according to their molecular properties, fate, and effects by considering additional ecotoxicological parameters in the TyPol method - Harouna Traoré; Olivier Crouzet; Laure Mamy; Christine Sireyjol; Virginie Rossard; Rémi Servien; Eric Latrille; Fabrice Martin-Laurent; Dominique Patureau; Pierre Benoit (Environmental Science and Pollution Research, 2018)

Multistage crack seal vein and hydrothermal Ni enrichment in serpentinized ultramafic rocks (Koniambo massif, New Caledonia) - Michel Cathelineau; Andrey Myagkiy; Benoit Quesnel; Marie-Christine Boiron; Pierre Gautier; Philippe Boulvais; Marc Ulrich; Laurent Truche; Fabrice Golfier; Maxime Drouillet (Mineralium Deposita, 2017)

Environmental determinants of the Mycobacterium bovis concomitant infection in cattle and badgers in France - Malika Bouchez-Zacria; Aurélie Courcoul; Pierre Jabert; Céline Richomme; Benoit Durand (European Journal of Wildlife Research, 2017)

Three glycosylated serine‐rich repeat proteins play a pivotal role in adhesion and colonization of the pioneer commensal bacterium, Streptococcus salivarius - Benoit Couvigny; Nicolas Lapaque; Lionel Rigottier‐Gois; Alain Guillot; Sophie Chat; Thierry Meylheuc; Saulius Kulakauskas; Manfred Rohde; Michel‐Yves Mistou; Pierre Renault; Joel Doré; Romain Briandet; et al. (Environmental Microbiology, 2017)
Summary Bacterial adhesion is a critical step for colonization of the host. The pioneer colonizer and commensal bacterium of the human gastrointestinal tract, Streptococcus salivarius , has strong adhesive properties but the molecular determinants of this adhesion remain uncharacterized. Serine‐rich repeat (SRR) glycoproteins are a family of adhesins that fulfil an important role in adhesion. In general, Gram‐positive bacterial genomes have a unique SRR glycoprotein‐encoding gene. We demonstrate that S. salivarius expresses three large and glycosylated surface‐exposed proteins – SrpA, SrpB and SrpC – that show characteristics of SRR glycoproteins and are secreted through the accessory SecA2/Y2 system. Two glycosyltransferases – GtfE/F – encoded outside of the secA2 / Y2 locus, unusually, perform the first step of the sequential glycosylation process, which is crucial for SRR activity. We show that SrpB and SrpC play complementary adhesive roles involved in several steps of the colonization process: auto‐aggregation, biofilm formation and adhesion to a variety of host epithelial cells and components. We also show that at least one of the S. salivarius SRR glycoproteins is important for colonization in mice. SrpA, SrpB and SrpC are the main factors underlying the multifaceted adhesion of S. salivarius and, therefore, play a major role in host colonization.

Virus-induced gene silencing in Rauwolfia species - Cyrielle Corbin; Florent Lafontaine; Liuda Johana Sepúlveda; Ines Carqueijeiro; Martine Courtois; Arnaud Lanoue; Thomas Dugé de Bernonville; Sébastien Besseau; Gaëlle Glévarec; Nicolas Papon; Lucia Atehortúa; Nathalie Giglioli-Guivarc’h; et al. (Protoplasma, 2017)

Virus-induced gene silencing of the two squalene synthase isoforms of apple tree (Malus × domestica L.) negatively impacts phytosterol biosynthesis, plastid pigmentation and leaf growth - Sandra M. Navarro Gallón; Carolina Elejalde-Palmett; Dimitri Daudu; Franziska Liesecke; Frédéric Jullien; Nicolas Papon; Thomas Dugé de Bernonville; Vincent Courdavault; Arnaud Lanoue; Audrey Oudin; Gaëlle Glévarec; Olivier Pichon; et al. (Planta, 2017)

Geochemical behavior of ultramafic waste rocks with carbon sequestration potential: a case study of the Dumont Nickel Project, Amos, Québec - El Hadji Babacar Kandji; Benoit Plante; Bruno Bussière; Georges Beaudoin; Pierre-Philippe Dupont (Environmental Science and Pollution Research, 2017)

Fate and impact of pesticides: new directions to explore - Céline Pelosi; Enrique Barriuso; Carole Bedos; Pierre Benoit; Laure Mamy; Christian Mougin (Environmental Science and Pollution Research, 2017)

Fresh and in vitro osteodifferentiated human amniotic membrane, alone or associated with an additional scaffold, does not induce ectopic bone formation in Balb/c mice - Romain Laurent; Aurélie Nallet; Benoit de Billy; Laurent Obert; Laurence Nicod; Christophe Meyer; Pierre Layrolle; Narcisse Zwetyenga; Florelle Gindraux (Cell and Tissue Banking, 2017)

Post-harvest banana peel splitting as a function of relative humidity storage conditions - Pierre Brat; Mathieu Lechaudel; Léa Segret; Raphaël Morillon; Olivier Hubert; Olivier Gros; Frédéric Lambert; Sophie Benoit; Christophe Bugaud; Frédéric Salmon (Acta Physiologiae Plantarum, 2016)

Impact of soil compaction on soil biodiversity – does it matter in urban context? - Cédric Devigne; Pierre Mouchon; Benoit Vanhee (Urban Ecosystems, 2016)

Influence of bottom trawling on sediment resuspension in the ‘Grande-Vasière’ area (Bay of Biscay, France) - Baptiste Mengual; Florence Cayocca; Pierre Le Hir; Robin Draye; Pascal Laffargue; Benoit Vincent; Thierry Garlan (Ocean Dynamics, 2016)

Old nurses always die: impacts of nurse age on local plant richness - Fateh Amghar; Estelle Forey; Benoit Richard; Blaise Touzard; Souhila Laddada; Lakhdar Brouri; Estelle Langlois; Pierre Margerie (Plant Ecology, 2016)

Transport of organic contaminants in subsoil horizons and effects of dissolved organic matter related to organic waste recycling practices - Florian Chabauty; Valérie Pot; Marjolaine Bourdat-Deschamps; Nathalie Bernet; Christophe Labat; Pierre Benoit (Environmental Science and Pollution Research, 2016)

Evaluating the genetic effects of the invasive O cenebra inornata on the native oyster drill O cenebra erinacea - Eric Pante; Pierre‐Yves Pascal; Vanessa Becquet; Amélia Viricel; Benoit Simon‐Bouhet; Pascale Garcia (Marine Ecology, 2015)
Studies focusing on the effect of invasive species on the genetic diversity of native marine invertebrates remain scant. Here we report diversity among French populations of the intertidal gastropod Ocenebra erinacea (Linnaeus, 1758) sampled in the presence and absence of the invasive Ocenebra inornata (Recluz, 1851). Between 1999 and 2004, a total of 352 individuals of O. erinacea was collected from 15 sites (five of which had the invasive present) and was genotyped at the mitochondrial locus Cytochrome Oxidase 1 ( cox1 ). No statistical difference was observed between polymorphism levels recorded within native populations exposed to the invasive, compared with populations sampled in the absence of O . inornata . No sign of native population decline was detected in response to the invader. While significant shifts in native O . erinacea population sizes have previously been reported in the literature, genetic effects may take longer to accumulate, or may be undetectable without a larger panel of genetic markers. By contrast, large genetic distances and significant population differentiation were recorded between Atlantic and Mediterranean O . erinacea samples, suggesting that these populations have distinct evolutionary histories. Comparison of genetic divergence within the closely related genus Nucella suggests that the Atlantic populations of O . erinacea and those from Thau Lagoon in the Mediterranean may belong to different species or subspecies.

Lead exposure through consumption of big game meat in Quebec, Canada: risk assessment and perception - Richard Coovi Fachehoun; Benoit Lévesque; Pierre Dumas; Antoine St-Louis; Marjolaine Dubé; Pierre Ayotte (Food Additives & Contaminants: Part A, 2015)

Rain regime and soil type affect the C and N dynamics in soil columns that are covered with mixed-species mulches - Akhtar Iqbal; Sohaib Aslam; Gonzague Alavoine; Pierre Benoit; Patricia Garnier; Sylvie Recous (Plant and Soil, 2015)

Prediction of the Fate of Organic Compounds in the Environment From Their Molecular Properties: A Review - Laure Mamy; Dominique Patureau; Enrique Barriuso; Carole Bedos; Fabienne Bessac; Xavier Louchart; Fabrice Martin-laurent; Cecile Miege; Pierre Benoit (Critical Reviews in Environmental Science and Technology, 2015)

Identification of a human ABCC10 orthologue in Catharanthus roseus reveals a U12-type intron determinant for the N-terminal domain feature - TAISSIR EL GUIZANI; CLOTILDE GUIBERT; SAÏDA TRIKI; BENOIT ST-PIERRE; ERIC DUCOS (Journal of Genetics, 2014)

The MISTIGRI thermal infrared project: scientific objectives and mission specifications - Jean-Pierre Lagouarde; Michel Bach; José A. Sobrino; Gilles Boulet; Xavier Briottet; Selma Cherchali; Benoit Coudert; Isabelle Dadou; Gérard Dedieu; Philippe Gamet; Olivier Hagolle; Frédéric Jacob; et al. (International Journal of Remote Sensing, 2013)

Groundwater Pollution and Quality Monitoring Approaches at the European Level - Matteo Balderacchi; Pierre Benoit; Philippe Cambier; Ole Martin Eklo; Alessandro Gargini; Alexandra Gemitzi; Melike Gurel; Bjørn Kløve; Zoran Nakic; Elena Predaa; Stanko Ruzicic; Przemysław Wachniew; et al. (Critical Reviews in Environmental Science and Technology, 2013)

Analysis of stomach bacterial communities in Australian feral horses - Benoit St-Pierre; Gabriel de la Fuente; Sean O’Neill; André-Denis G. Wright; Rafat Al Jassim (Molecular Biology Reports, 2013)

Including the Drag Effects of Canopies: Real Case Large-Eddy Simulation Studies - Pierre Aumond; Valery Masson; Christine Lac; Benoit Gauvreau; Sylvain Dupont; Michel Berengier (Boundary-Layer Meteorology, 2013)

Mineralogy, geochemistry and petrogenesis of the recent magmatic formations from Mbengwi, a continental sector of the Cameroon Volcanic Line (CVL), Central Africa - Benoît Joseph Mbassa; Emmanuel Njonfang; Mathieu Benoit; Pierre Kamgang; Michel Grégoire; Stephanie Duchene; Pierre Brunet; Bekoa Ateba; Félix M. Tchoua (Mineralogy and Petrology, 2012)

Where do adaptive shifts occur during invasion? A multidisciplinary approach to unravelling cold adaptation in a tropical ant species invading the Mediterranean area - Olivier Rey; Arnaud Estoup; Merav Vonshak; Anne Loiseau; Simon Blanchet; Luis Calcaterra; Lucila Chifflet; Jean‐Pierre Rossi; Gaël J. Kergoat; Julien Foucaud; Jérôme Orivel; Maurice Leponce; et al. (Ecology Letters, 2012)
Evolution may improve the invasiveness of populations, but it often remains unclear whether key adaptation events occur after introduction into the recipient habitat (i.e. post‐introduction adaptation scenario), or before introduction within the native range (i.e. prior‐adaptation scenario) or at a primary site of invasion (i.e. bridgehead scenario). We used a multidisciplinary approach to determine which of these three scenarios underlies the invasion of the tropical ant Wasmannia auropunctata in a Mediterranean region (i.e. Israel). Species distribution models ( SDM ), phylogeographical analyses at a broad geographical scale and laboratory experiments on appropriate native and invasive populations indicated that Israeli populations followed an invasion scenario in which adaptation to cold occurred at the southern limit of the native range before dispersal to Israel. We discuss the usefulness of combining SDM , genetic and experimental approaches for unambiguous determination of eco‐evolutionary invasion scenarios.

A single gene encodes isopentenyl diphosphate isomerase isoforms targeted to plastids, mitochondria and peroxisomes in Catharanthus roseus - Grégory Guirimand; Anthony Guihur; Michael A. Phillips; Audrey Oudin; Gaëlle Glévarec; Céline Melin; Nicolas Papon; Marc Clastre; Benoit St-Pierre; Manuel Rodríguez-Concepción; Vincent Burlat; Vincent Courdavault (Plant Molecular Biology, 2012)

Food sources used by sediment meiofauna in an intertidal Zostera noltii seagrass bed: a seasonal stable isotope study - Benoit Lebreton; Pierre Richard; Robert Galois; Gilles Radenac; Amel Brahmia; Géraldine Colli; Marig Grouazel; Cyril André; Gaël Guillou; Gérard F. Blanchard (Marine Biology, 2012)

Transferrin Adsorption onto PLGA Nanoparticles Governs Their Interaction with Biological Systems from Blood Circulation to Brain Cancer Cells - Jiang Chang; Archibald Paillard; Catherine Passirani; Marie Morille; Jean-Pierre Benoit; Didier Betbeder; Emmanuel Garcion (Pharmaceutical Research, 2012)

Molecular cloning and functional characterization of Catharanthus roseus hydroxymethylbutenyl 4-diphosphate synthase gene promoter from the methyl erythritol phosphate pathway - Olivia Ginis; Vincent Courdavault; Céline Melin; Arnaud Lanoue; Nathalie Giglioli-Guivarc’h; Benoit St-Pierre; Martine Courtois; Audrey Oudin (Molecular Biology Reports, 2012)

High-intensity sprint fatigue does not alter constant-submaximal velocity running mechanics and spring-mass behavior - Jean-Benoit Morin; Katja Tomazin; Pierre Samozino; Pascal Edouard; Guillaume Y. Millet (European Journal of Applied Physiology, 2012)

A New Cell for Electrical Conductivity Measurement on Saturated Samples at Upper Crust Conditions - Marie Violay; Benoit Gibert; Pierre Azais; Philippe A. Pezard; Gérard Lods (Transport in Porous Media, 2012)

Treatment of 9L Gliosarcoma in Rats by Ferrociphenol-Loaded Lipid Nanocapsules Based on a Passive Targeting Strategy via the EPR Effect - Ngoc Trinh Huynh; Marie Morille; Jerome Bejaud; Pierre Legras; Anne Vessieres; Gerard Jaouen; Jean-Pierre Benoit; Catherine Passirani (Pharmaceutical Research, 2011)

Optimized assay and storage conditions for enzyme activity profiling of ectomycorrhizae - Karin Pritsch; Pierre Emanuel Courty; Jean-Louis Churin; Benoit Cloutier-Hurteau; Muhammad Arif Ali; Coralie Damon; Myriam Duchemin; Simon Egli; Jana Ernst; Laurence Fraissinet-Tachet; Francisco Kuhar; Elvira Legname; et al. (Mycorrhiza, 2011)

Functional analysis of the DAT gene promoter using transient Catharanthus roseus and stable Nicotiana tabacum transformation systems - Abdullah Makhzoum; Geneviève Petit-Paly; Benoit St. Pierre; Mark A. Bernards (Plant Cell Reports, 2011)

Carbon, nitrogen and Greenhouse gases budgets over a four years crop rotation in northern France - Benjamin Loubet; Patricia Laville; Simon Lehuger; Eric Larmanou; Christophe Fléchard; Nicolas Mascher; Sophie Genermont; Romain Roche; Rossana M. Ferrara; Patrick Stella; Erwan Personne; Brigitte Durand; et al. (Plant and Soil, 2011)

Toxicological Study and Efficacy of Blank and Paclitaxel-Loaded Lipid Nanocapsules After i.v. Administration in Mice - José Hureaux; Frédéric Lagarce; Frédéric Gagnadoux; Marie-Christine Rousselet; Valérie Moal; Thierry Urban; Jean-Pierre Benoit (Pharmaceutical Research, 2010)

Local Delivery of Ferrociphenol Lipid Nanocapsules Followed by External Radiotherapy as a Synergistic Treatment Against Intracranial 9L Glioma Xenograft - Emilie Allard; Delphine Jarnet; Anne Vessières; Sandrine Vinchon-Petit; Gérard Jaouen; Jean-Pierre Benoit; Catherine Passirani (Pharmaceutical Research, 2010)

Morphology and nuclear markers reveal extensive mitochondrial introgressions in the Iberian Wall Lizard species complex - JULIEN P. RENOULT; PHILIPPE GENIEZ; PAUL BACQUET; LAURE BENOIT; PIERRE‐ANDRÉ CROCHET (Molecular Ecology, 2009)
Mitochondrial markers are still often used alone to identify evolutionary units, despite widespread evidence for processes such as incomplete lineage sorting or introgressive hybridization that may blur past population history. The combination of mitochondrial DNA data with other sources of information (morphology, nuclear genes) is a powerful tool to reveal when and why mitochondrial markers are potentially misleading. In this study, we evaluate the performance of mtDNA markers to unravel the evolutionary history of Spanish lizards from the Podarcis hispanicus species complex. We first uncover several cases of discordance between morphological and mitochondrial data in delimitation of taxa. To assess the origin of these discordances, we analysed the same populations using several independent nuclear loci. Both morphological and nuclear markers identified the same three evolutionary units in the region, while mitochondrial data revealed four deeply divergent lineages. We suggest here that the most likely scenario to explain this discordance is ancient mitochondrial introgression originating from a fourth evolutionary unit presently absent from the study area. Notably, this resulted in a complete replacement of the original lineage in a large part of the distribution of one of the taxa investigated. We discuss the potential evolutionary scenarios leading to this complete mitochondrial replacement and suggest why the previous studies have failed to recover the correct history of this species complex.

Optimization of the transient transformation of Catharanthus roseus cells by particle bombardment and its application to the subcellular localization of hydroxymethylbutenyl 4-diphosphate synthase and geraniol 10-hydroxylase - Grégory Guirimand; Vincent Burlat; Audrey Oudin; Arnaud Lanoue; Benoit St-Pierre; Vincent Courdavault (Plant Cell Reports, 2009)

Proteins prenylated by type I protein geranylgeranyltransferase act positively on the jasmonate signalling pathway triggering the biosynthesis of monoterpene indole alkaloids in Catharanthus roseus - Vincent Courdavault; Vincent Burlat; Benoit St-Pierre; Nathalie Giglioli-Guivarc’h (Plant Cell Reports, 2009)

Effects of muscular biopsy on the mechanics of running - Jean-Benoit Morin; Pierre Samozino; Léonard Féasson; André Geyssant; Guillaume Millet (European Journal of Applied Physiology, 2009)

Spatial distribution and hormonal regulation of gene products from methyl erythritol phosphate and monoterpene-secoiridoid pathways in Catharanthus roseus - Audrey Oudin; Samira Mahroug; Vincent Courdavault; Nadège Hervouet; Charles Zelwer; Manuel Rodríguez-Concepción; Benoit St-Pierre; Vincent Burlat (Plant Molecular Biology, 2007)

Cellular and sub-cellular organisation of the monoterpenoid indole alkaloid pathway in Catharanthus roseus - Samira Mahroug; Vincent Burlat; Benoit St-Pierre (Phytochemistry Reviews, 2007)

The determinants of prevalence of health complaints among young competitive swimmers - Benoit Lévesque; Jean-François Duchesne; Suzanne Gingras; Robert Lavoie; Denis Prud’Homme; Emmanuelle Bernard; Louis-Philippe Boulet; Pierre Ernst (International Archives of Occupational and Environmental Health, 2006)

Pegylated Nanocapsules Produced by an Organic Solvent-Free Method: Evaluation of their Stealth Properties - Arnaud Béduneau; Patrick Saulnier; Nicolas Anton; François Hindré; Catherine Passirani; Holisoa Rajerison; Nicolas Noiret; Jean-Pierre Benoit (Pharmaceutical Research, 2006)

Epidermis is a pivotal site of at least four secondary metabolic pathways in Catharanthus roseus aerial organs - Samira Mahroug; Vincent Courdavault; Martine Thiersault; Benoit St-Pierre; Vincent Burlat (Planta, 2006)

CaaX-prenyltransferases are essential for expression of genes involvedin the early stages of monoterpenoid biosynthetic pathwayin Catharanthus roseus cells - Vincent Courdavault; Martine Thiersault; Martine Courtois; Pascal Gantet; Audrey Oudin; Pierre Doireau; Benoit St-Pierre; Nathalie Giglioli-Guivarc’h (Plant Molecular Biology, 2005)

Influence of 5-Fluorouracil-Loaded Microsphere Formulation on Efficient Rat Glioma Radiosensitization - Valérie-Gaëlle Roullin; Martine Mege; Laurent Lemaire; Jean-Pierre Cueyssac; Marie-Claire Venier-Julienne; Philippe Menei; Erik Gamelin; Jean-Pierre Benoit (Pharmaceutical Research, 2004)

Seismic Microzonation: A Comparison between Geotechnical and Seismological Approaches in Pointe-à-Pitre (French West Indies) - Benoit LeBrun; Anne-Marie Duval; Pierre-Yves Bard; Olivier Monge; Myriam Bour; Sylvain Vidal; Hubert Fabriol (Bulletin of Earthquake Engineering, 2004)

A New Mathematical Model Quantifying Drug Release from Bioerodible Microparticles Using Monte Carlo Simulations - Juergen Siepmann; Nathalie Faisant; Jean-Pierre Benoit (Pharmaceutical Research, 2002)

A Novel Phase Inversion-Based Process for the Preparation of Lipid Nanocarriers - Béatrice Heurtault; Patrick Saulnier; Brigitte Pech; Jacques-Emile Proust; Jean-Pierre Benoit (Pharmaceutical Research, 2002)

The complex regulation of ferredoxin/thioredoxin-related genes by light and the circadian clock - Stéphane D. Lemaire; Mariana Stein; Emmanuelle Issakidis-Bourguet; Eliane Keryer; Vanina Benoit; Bernard Pineau; Catherine Gérard-Hirne; Myroslawa Miginiac-Maslow; Jean-Pierre Jacquot (Planta, 1999)

Why Does PEG 400 Co-Encapsulation Improve NGF Stability and Release from PLGA Biodegradable Microspheres? - Jean-Manuel Péan; Franck Boury; Marie-Claire Venier-Julienne; Philippe Menei; Jacques-Emile Proust; Jean-Pierre Benoit (Pharmaceutical Research, 1999)

A YAC contig encompassing the 11q14.3 breakpoint of a translocation associated with schizophrenia, and including the tyrosinase gene - Joëlle Petit; Pierre Boisseau; Laurence Taine; Bruno Gauthier; Benoit Arveiler (Mammalian Genome, 1999)

Influence of the amino acid sequence on the MUC5AC motif peptide O-Glycosylation by Human gastric UDP-GalNAc:polypeptide N-acetylgalactosaminyltransferase(s) - Sylviane Hennebicq; Daniel Tetaert; Benoit Soudan; Arnold Boersma; Gilbert Briand; Colette Richet; Jean Gagnon; Pierre Degand (Glycoconjugate Journal, 1998)

Evidence for a Substrate-Borne Sex Pheromone in the Parasitoid Wasp Trichogramma brassicae - Francois Pompanon; Benoit De Schepper; Yvan Mourer; Pierre Fouillet; Michel Bouletreau (Journal of Chemical Ecology, 1997)

Tensioactivity and Supramolecular Organization of the Palmitoyl Prodrug of Timolol - Brigitte Pech; Jacques-Emile Proust; Yves Bouligand; Jean-Pierre Benoit (Pharmaceutical Research, 1997)